Формування художньо-естетичного досвіду учнівської молоді: особистісно-орієнтований сегмент - Горбенко Сергій; Horbenko Serhii (Видавництво «Код», 2025)
Резюме. У статті розкриваються деякі аспекти процесу формування художньо-естетичного досвіду учнів різних вікових категорій на основі особистісного підходу. Означений феномен трактується в контексті «світу мистецтв», на перетині зовнішнього (художнього) і внутрішнього (переживання) та емоційно-образного пізнання мистецьких явищ. Відстоюється думка про те, що саме через переживання, емоції, почуття, досягнення дитиною катарсичного стану при спілкуванні з творами мистецтва набувається художньо-естетичний досвід. Висвітлюються ряд специфічних умов особистісноорієнтованого спрямування, що сприяють ефективності формування означеного феномену.

Abstract. The article focuses on the problem of shaping the artistic and aesthetic experience of students of different age groups in general secondary, art, and music schools. This concept is viewed as an aesthetic category reflecting a person’s sensory, value-spiritual, and need-driven attitude toward reality. It is primarily based on the ability to experience emotions, to feel life situations, to distinguish between the beautiful and the ugly, and to fully perceive and comprehend works of various kinds of art. The paper argues for the necessity of several conditions, among which one of the most important is an individual’s ability to adequately perceive works of art (musical, visual, choreographic, literary); the development of the sensory sphere, imaginative thinking, and emotionality, which lead the personality to inner experiences and spiritual catharsis. Spiritualcathartic activity is understood here as a person’s readiness to make a conscious choice of their place in life and the ability to fully reveal and realize their innate artistic and creative potential. The study shows that through catharsis students assimilate universal human values transmitted by art; by enriching their own value sphere, they become capable of experiencing spiritual purification and uplift and of building relationships among the participants of the educational process on the basis of mutual understanding, respect, and creative cooperation. Attention is drawn to person-centered art education as an important psychological and pedagogical issue and to the creation of an appropriate educational environment where innovative approaches, diverse forms of joint activity between teacher and student, and dialogic, respectful communication are effectively implemented, which leads to the development of students’ personal artistic and aesthetic formations. The mechanisms for developing artistic and aesthetic experience are seen in students’ ability to freely express their impressions, views, and opinions during the process of artistic creation; in fostering an atmosphere of active learning and natural selfexpression; and in promoting the self-development of the individual on the basis of subject-tosubject relationships between students and teacher.
Formation of the artistic and aesthetic experience of school youth: a person-centered segment
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-16?authuser=0
Keywords: учнівська молодь; мистецтво; сприймання; художній досвід; особистісний підхід; емоційна сфера